KEADILAN RESTORATIF DALAM SISTEM PERADILAN PIDANA INDONESIA - Auliah Andika Rukman (Muhammadiyah Makassar University, 2023)
ABSTRACTThis research examines the implementation of restorative justice in Indonesia's criminal justice system. Restorative justice is a novel approach to resolving criminal cases that emphasizes justice and balance for both offenders and victims. The concept has its roots in indigenous communities in Indonesia and has been recognized through various regulations and guidelines at the police, prosecution, and judiciary levels.The research adopts a juridical normative method with a descriptive approach, analyzing secondary sources such as literature, legislation, and government policies related to restorative justice. The findings reveal that the Indonesian police force (Polri) has the authority to formulate new concepts in criminal law enforcement that accommodate societal norms and values. The public prosecutor's office (Kejaksaan) has resolved numerous cases through restorative justice, focusing on rehabilitation and reconciliation for both victims and offenders.In the judiciary, the principles of restorative justice are acknowledged and practiced through various regulations and circulars issued by the Supreme Court. Courts promote peace-making between offenders and victims and prioritize restorative justice in their judgments. However, the application of restorative justice has certain limitations and prerequisites.The research highlights that restorative justice continues to be developed and implemented to achieve the goals of justice, certainty, and utility in Indonesia's criminal justice system. The approach offers a humane alternative and aims to repair harm, reconcile parties, and restore harmony within society. Nonetheless, its implementation is subject to specific criteria and may not be applicable in all cases. The ongoing refinement of restorative justice in Indonesia seeks to enhance the overall fairness and effectiveness of the criminal justice system.